Evidence on the Trade-Off between Real Activities Manipulation and Accrual-Based Earnings Management - Zang, Amy Y. (The Accounting Review, 2012)
ABSTRACT I study whether managers use real activities manipulation and accrual-based earnings management as substitutes in managing earnings. I find that managers trade off the two earnings management methods based on their relative costs and that managers adjust the level of accrual-based earnings management according to the level of real activities manipulation realized. Using an empirical model that incorporates the costs associated with the two earnings management methods and captures managers' sequential decisions, I document large-sample evidence consistent with managers using real activities manipulation and accrual-based earnings management as substitutes. Data Availability: Data are available from public sources indicated in the text.